2008
DOI: 10.1007/s11284-008-0543-8
|View full text |Cite
|
Sign up to set email alerts
|

Re‐established mutualism in a seed‐dispersal system consisting of native and introduced birds and plants on the Bonin Islands, Japan

Abstract: The disruption of plant-animal interactions such as seed dispersal is one of the most critical effects of biological invasions. To understand the role of introduced species in current seed-dispersal systems, we conducted fecal analyses of the most common resident land birds on the Bonin Islands, Japan, and estimated their relative importance as seed-dispersal agents. Two native birds, the brown-eared bulbul and the Bonin Islands white-eye, and the introduced Japanese white-eye were the primary seed dispersers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 31 publications
4
49
0
Order By: Relevance
“…In recent years, this growing realization has lifted the focus of conservation efforts from species to ecosystems [1,19]. While there is an increasing number of studies documenting different aspects of the dispersal of native and invasive plants by frugivores [10,20], the consequences of the integration of alien plants into seed dispersal networks has been poorly explored [21]. By contrast, several studies have evaluated the impact of alien plants upon pollination networks.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this growing realization has lifted the focus of conservation efforts from species to ecosystems [1,19]. While there is an increasing number of studies documenting different aspects of the dispersal of native and invasive plants by frugivores [10,20], the consequences of the integration of alien plants into seed dispersal networks has been poorly explored [21]. By contrast, several studies have evaluated the impact of alien plants upon pollination networks.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, the contribution of alien birds to seed dispersal of native plants is unexpectedly small (Kelly et al 2006 ). In the Bonin Islands, Kawakami et al (2009) found that introduced whiteeyes appear to compensate for extinct native seed dispersers.…”
Section: Can Invasive Alien Species Replace Extinct or Declining Natimentioning
confidence: 99%
“…Staddon et al 2010). The negative effect of species extinctions on seed dispersal processes could be lessened if other species are able to compensate for those that have been lost (Kawakami et al 2009). New Zealand lacks native land mammals (apart from three bat species), but now hosts 32 species of introduced mammals, most of which are considered pests (King 2005).…”
Section: Introductionmentioning
confidence: 99%